2015
DOI: 10.1186/s13395-014-0026-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of Sox6 in zebrafish muscle fiber type specification

Abstract: BackgroundThe transcription factor Sox6 has been implicated in regulating muscle fiber type-specific gene expression in mammals. In zebrafish, loss of function of the transcription factor Prdm1a results in a slow to fast-twitch fiber type transformation presaged by ectopic expression of sox6 in slow-twitch progenitors. Morpholino-mediated Sox6 knockdown can suppress this transformation but causes ectopic expression of only one of three slow-twitch specific genes assayed. Here, we use gain and loss of function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…We first determined the expression pattern of the four genes by in situ hybridization both in whole embryos at 24 hpf (hours post-fertilization), and in axial sections to distinguish the localization of these transcripts in slow and fast muscles31. Examination of more than 50 embryos hybridized with each probe from two independent experiments indicated that, in all these embryos, the expression of these genes could be detected in the somites.…”
Section: Resultsmentioning
confidence: 99%
“…We first determined the expression pattern of the four genes by in situ hybridization both in whole embryos at 24 hpf (hours post-fertilization), and in axial sections to distinguish the localization of these transcripts in slow and fast muscles31. Examination of more than 50 embryos hybridized with each probe from two independent experiments indicated that, in all these embryos, the expression of these genes could be detected in the somites.…”
Section: Resultsmentioning
confidence: 99%
“…The optical transparency of the zebrafish larva facilitates the visualization of adipocytes by Nile Red staining in whole-mount preparations (Flynn et al, 2009). Loss of Sox6 function in zebrafish has previously been shown to disrupt the differentiation of fast-twitch skeletal muscle fibers, but effects on adipocytes have not been addressed (Jackson et al, 2015). For the current study, control and sox6 homozygous null mutant larvae were stained with Oil Red O (Fig.…”
Section: Loss Of Sox6 Decreases Adipogenesis In Zebrafish Larvaementioning
confidence: 99%
“…As a consequence, Sox6 -null mouse muscle displays increased levels of MyHC-I and a general switch toward a slower phenotype (Hagiwara et al., 2007, An et al., 2011, Quiat et al., 2011). Of note, studies in zebrafish have shown that Sox6 is restricted to fast-twitch fibers during embryonic muscle development and that ectopic Sox6 expression in adaxial cells (the slow muscle progenitors in zebrafish) leads to the silencing of slow-twitch genes (such as the slow MyHC isoform smyhc1 and the transcription factor prox1a ) (von Hofsten et al., 2008, Wang et al., 2011, Jackson et al., 2015). …”
Section: Introductionmentioning
confidence: 99%